Wayne W. Parrish papers - Parrish, Wayne W. (Wayne William), 1907-1984.
Correspondence, memoranda, reports, speeches and writings, commemorative programs, airline insignia, logos, schedules, tickets, and other aeronautical memorabilia, photographs, and printed matter documenting Parrish's role as founder and president of American Aviation Publications (AAP). Includes correspondence with airline executives, aircraft manufacturers, and pilots relating to political, technical, labor, and business issues in aviation. Also includes material on Parrish's World War II experiences as a journalist inspecting the results of Allied bombing of Germany; Rockwell International's flight to traverse both poles (1966) and other historic flights; and Parrish's reports on commercial aviation in the Soviet Union.
Aviation journalist and publisher.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: American Aviation Publications; Rockwell International; Aeronautics; Aeronautics -- Flights; Aeronautics -- Periodicals; Aeronautics, Commercial -- Soviet Union; Aircraft industry -- United States; Airlines -- Soviet Union; Airlines -- United States; Bombardment -- Germany; Journalism, Aeronautical -- United States; Polar regions -- Aerial exploration; World War, 1939-1945 -- Aerial operations, Allied; World War, 1939-1945 -- Journalists; Journalists; Publishers